An institutional perspective on entrepreneurship in a conflict environment: evidence from Pakistan. Issue 5 (1st August 2016) - Warren, Lorraine; Muhammad, Noor; Ullah, Farid
Abstract : Purpose: In this paper, an institutional perspective is used to examine the different kinds of pressures on entrepreneurs manifest in a conflict environment. The study investigates how they respond to the conflict and establish legitimacy for their entrepreneurship in the challenging context of the north western areas of Pakistan. Design/methodology/approach: In this study, a qualitative approach is taken based on semi-structured interviews from 16 different firms in the SWAT valley. Findings: The entrepreneurs undertake different strategies towards dealing with conflict and establishing legitimacy. These strategies are identified and examined in relation to the interactions between entrepreneurial behaviour and institutional pressures. Research limitations/implications: Qualitative research on a small sample inevitably presents a limitation on the generalisability of this work. Further research could employ quantitative methods to address this issue. One particular location is studied, so future research could be carried out in other countries or regions with similar problems. Practical implications: The study may have value for policy makers who need to know more about how to support ongoing businesses in difficult regions. Originality/value: A new dimension is added to institutional theory through its application in the very uncertain environment between all out war and ongoing violence, identifying the possibility of weak agency for institutional change. Further, the study contributes to the growing body of literature on entrepreneurship in conflict environments.